Analysis of the results alteration of the elite female high jumpers during the long-term training process - Zilinskiene, N.; Radziukynas, D. (Acta Kinesiologiae Universitatis Tartuensis, 2011)
Aim of Research: To determine general consistency and individual peculiarities, which were observed during the long-term training process of the elite female high jumpers. Subjects: The Elite Lithuanian and World Female High Jumpers (n=13). Methods: Analysis of literature sources and documentation; comparative pedagogical analysis; statistical analysis. Results: It was determined that the Elite Female High Jumpers achieve their best results at the age of 25.92±0.94. Their average height is 1.81±0.02 m and the average weight- 61.83±1.41 kg. It was determined that the sport results of the World`s best Female High Jumpers at certain preparation stages would not improve evenly. The saltatory increase of results was determined on the Initial Preparation Stage (12-17 years old) going up from 1.40±0.06 m till 1.84±0.02 m (p<0.001). At the Special Preparation Stage (18-21 year old) the sport results increase apace and start improving from 1.84±0.02 m till 1.94±0.03 m (p<0.001). The Stage of High Sport Results Pursuit (22-26 m.) is slower, yet results improve from 1.95±0.02 m till 2.01±0.02 m (p<0.001). At the Stage of High Sport Results Maintenance (27-32 m.) the rate of sport results is kept stabile fluctuating from 1.99±0.02 m till 2.01±0.01 m (p<0.05). We could state that the sport results progress differently depending on the factor of pubescence, especially on the Initial Preparation Stage, the training programs, the competition systems, the organism adaptation to the physical strain, the readiness, the social factors, etc. It was determined that dur ng the annual training cycle the fluctuation of sport results is individual and wavy, i.e. every two or three competitions they increase, but after decrease. Peculiarities of individual sport results fluctuation are depend on preparedness, technique, condition, motivation, competition level, competition conditions, etc. Thus we could conclude that the objective consistency and peculiarities for alteration of sports results exist, and once acknowledged, would allow a better selection of gifted athletes, provide training methodology and means, help with competition planning as well as forecast of sport results evolution.